Entomo-Industry of Hermetia Illucens - A. B. Artakhov (Вестник Российского экономического университета имени Г. В. Плеханова)
Innovation in production use of insects allows us to speak about entomo-industry, which could cause in the future a drop in the relative cost of food. On the basis of biotechnology by using the fly Hermetia illucens the article draws theoretical and applied economic conclusions. Larvae of this fly by eating organic wastes during a few days can grow in hundred times and become a feed for animals, a basis for medicine or even a nutritious supplement, while their waste can become a fertilizer (zoo-humus). From means of labour they turn into the subject of labour with selfreproduction and solution to ecological problem, which can create the added value. In traditional livestock breeding fast transformation does not take place and animal acts mainly as the subject or means of labour. Commercialization of the technology can be achieved through development of module equipment for each of 9 processes and this can make it possible to purchase it stage by stage, depending on the need and resources. Due to this fact competitive advantage for technological entrepreneurship can be provided that can take one of the following three types: in the narrow sense (developing and selling equipment), in the broad sense (manufacturing the product with own equipment) and mixed one (manufacturing and selling of the equipment and finished product, joint work of the developer and user of the equipment). The author designed a synthetic graphic business-model of entomo-technological entrepreneurship. Logical schemes of waste treatment were put forward: centralized and decentralized. It was found out that for agricultural waste the decentralized scheme is more appropriate, as it implies treatment at the place of shaping and economizing on transportation. In Russia the process of commercialization of biotechnologies with the use of Hermetia illucens started in 2015, which is proven by patent activity. However, the market develops rather slowly.